Effect of Air Bubbles on Heat Transfer Coefficient in Turbulent Convection Flow (Journal of Engineering, 2017)
Experimental and numerical studies have been conducted for the effect of injected air bubbles on the heat transfer coefficient through the water flow in a vertical pipe under the influence of uniform heat flux. The investigated parameters were water flow rate of (10, 14 and 18) lit/min, air flow rate of (1.5, 3 and 4) lit/min for subjected heat fluxes of (27264, 36316 and 45398) W/m2. The energy, momentum and continuity equations were solved numerically to describe the motion of flow. Turbulence models k-ε was implemented. The mathematical model is using a CFD code Fluent (Ansys15). The water was used as continuous phase while the air was represented as dispersed. phase. The experimental work includes design, build and instrument a test rig for that purpose. Acircular vertical copper pipe test section of (length=0.7m, diameter= 0.05m, thickness= 1.5mm) is . designed and constructed, heated by an electrical heater fixed on its outer surface. Water . temperature at inlet is kept constant at (32°C). Water inlet and outlet temperatures, as well as radial temperature distribution within the pipe at seven sections along it between pipe surface and its center are measured. The results revealed that the secondary flow created by air bubbles havesignificant effects on heat transfer enhancement and temperature profile. It is observed, that averaged Nusselt number enhancement for low heat flux of 27264 W/m2 and 4 lit/min air bubbles was 33.3 % and 23% in numerical and experimental, respectively.